Factor structure and construct validity of the Generalized Anxiety Disorder 7-item (GAD-7) among Portuguese college students - Ana Bártolo; Sara Monteiro; Anabela Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: The Generalized Anxiety Disorder 7-item (GAD-7) scale has been presented as a reliable and valid measure to assess generalized anxiety symptoms in several clinical settings and among the general population. However, some researches did not support the original one-dimensional structure of the GAD-7 tool. Our main aim was to examine the factor structure of GAD-7 comparing the one-factor model fit with a two-factor model (3 somatic nature symptoms and 4 cognitive-emotional nature symptoms) in a sample of college students. This validation study with data collected cross-sectionally included 1,031 Portuguese college students attending courses in the six schools of the Polytechnic Institute of Coimbra, Coimbra, Portugal. Measures included the GAD-7, Hospital Anxiety and Depression Scale (HADS) and the University Student Risk Behaviors Questionnaire. Confirmatory factor analysis (CFA) procedures confirmed that neither factor structure was well fitting. Thus, a modified single factor model allowing the error terms of items associated with relaxing difficulties and irritability to covary was an appropriate solution. Additionally, this factor structure revealed configural and metric invariance across gender. A good convergent validity was found by correlating global anxiety and depression. However, this measure showed a weak association with consumption behaviors. Our results are relevant to clinical practice, since the comprehensive approach to GAD-7 contributes to knowing generalized anxiety symptoms trajectory and their correlates within the university setting.